The construction of the graphical image of the target functional and its use for the search for multivariant solutions of the inverse magneto-prospecting problem - Zeygelman, M. S.; Panchenko, N. V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2017)
For practical applications, we propose a technology for searching ordered sets of feasible solutions of the inverse magneto-prospecting problem. It is oriented towards using the elements of the guarantee approach, which is realized due to the construction and analysis of fairly broad communities of approximately equivalent solutions. One of the possible variants of this approach is considered, based on the idea of constructing the graphic structure of the target functional involved in the algorithms for automated selection. The necessary information is represented in the form of maps of the projection of the graphic structure. A technique for constructing such maps has been developed. The features of their application for organizing a purposeful search for the set of admissible solutions of the inverse problem are considered. An example of a multivariate approach for interpreting anomaly observations is given.